Relay the Right Way: Harnessing Heterogeneity in Sequential Team Production. (8th April 2015) - Collins, Sean
Abstract : How a manager chooses to organize teams is a question with substantial efficiency implications. This study reports evidence on how ordering of heterogenous team members impacts productivity and free riding in a sequential production task. A laboratory experiment permits exogenous reordering of team members by cost of contribution. Analyses suggest that team productivity is higher when low cost team members lead and less variable when low cost members both precede and follow high cost members (e.g., the conventional relay team order). Additionally, team members are found to respond in‐kind to the contributions of both predecessors and successors. Copyright © 2015 John Wiley & Sons, Ltd.